Good bacteria gone awry: probiotic-induced bacteremia in a vulnerable patient - a unique case report - Riddhi Machchhar; Ana Torres Hernandez; Christopher Meusburger; Prabhav Kashyap Godavarthy; Jithin Reddy Vennapusa; Christian Grant; Bassam Hasan; Michael Rothberg (Infectious Diseases and Herbal Medicine, 2025)
Probiotics have gained immense popularity as an over-the-counter supplement in recent years. Many people use probiotics to promote gastrointestinal and immunologic health. However, there is not much concrete evidence regarding the safety and efficacy of these ingested capsules of foreign bacterial content and their potential to become opportunistic pathogens. Special populations, such as immunocompromised patients, may try these supplements for their touted benefits and the label of being naturally occurring, but they can unknowingly cause undue harm to their health. Probiotics are unregulated supplements that cannot definitively claim to be the appropriate mixture of bacteria for diverse gut microbiomes, confirm the optimal dosage before adverse events are observed, or provide a number needed to harm as seen in other medical trials. Here, we present a case of a 69-year-old female with multiple comorbidities who presented with weakness and was found to have lactobacillus bacteremia due to bacterial transmigration of pathogens introduced through probiotic consumption. This incident highlights the increasing need for investigation regarding unregulated over-the-counter supplements, specifically probiotics, and their utility and safety. Along with emerging data regarding probiotics and their beneficial but sometimes harmful impact, our case aims to create a dialogue about when the use of adjuvants is appropriate and within which patient populations.